ҚОРАҚАЛПОҚ УСТЮРТИДА EUPHORBIA SCLEROCYATHIUM ЦЕНОПОПУЛИЯЛАРИНИНГ ТАРҚАЛГАН ҲУДУДЛАРИ ТАВСИФИ - Tamambetova, Sh.B. (SCIENCE and SOCIETY, 2024)
The article discusses the description and characteristics of the areas of Euphorbia sclerocyathium coenopopulations in Karakalpak Ustyurt. The geographical points and coordinates of the area, topography, soil composition of the territories of xenopopulation distribution are indicated. geographical points and coordinates of the area, topography, soil composition, territories of coenopopulation distribution. The climate of Ustyurt were indicated maximum and minimum temperature, total solar radiation, average annual precipitation, soil salinity.
Keywords: Euphorbia sclerocyathium; Ustyurt plateau; cenopopulation; maximum and minimum temperature; total solar radiation; average annual precipitation